PEMANFAATAN LIMBAH KAYU MERANTI RAWA (Shorea balangeran) UNTUK PEMBUATAN PAPAN PARTIKEL BERLAPIS ANYAMAN ROTAN (Utilizing Waste of Shorea balangeran Wood to Particle Board with Woven Rattan-Coated): Sarinah, D. Natalia Koroh, Grace Siska - JHT, Admin (Jurnal Hutan Tropika, 2015)
ABSTRACTMeranti (Shorea balangeran) is one of some species that grow well at peat swamp forest. Wood of meranti useful to furniture, kosen (window or door frame), board etc. Unfortunately, the waste of its wood processing is low valuable. Therefore, utilizing waste of meranti to particle board is the good idea. In order to strengthen the particle board, it could be coated by braided rattan. This research was aimed to determine the physical and mechanical properties of particle board that made from waste of meranti, using PVAc adhesive and coated by woven rattan. The research was conducted to campare particle board without woven rattan-coated (a1) and using woven rattan-coated (a2) with 20%, 30%, and 40% of adhesive level respectively. Research result show that using adhesive with level of 40% is better than 20% and 30% in the form of physical and mechanical properties and suitable with JIS 5908:2003 standard.Keywords : particle board, waste, physical and mechanical properties